The pattern of brittle deformation in Central America for an assessment of the seismo-tectonic framework - Mauro Agate; Francesco Caldareri; Luis Castillo; Amalia Garcia; Giuseppe Giunta; Luis Mixco; Jaime Requena; Carlos Rubi Tellez; Maynor Ruiz; Attilio Sulli; Abel Alexei Argueta-Platero; Heyddy Calderon; et al. (Journal of Maps)
A seismo-tectonic map depicting the principal structural elements of the northern Central American region has been meticulously crafted to characterize the tectonic setting and the individual seismo-tectonic structures of this area. This region is subject to heightened seismic activity, with a large number of medium-high Magnitude occurrences transpiring annually. This map is presented alongside an informative dataset wherein fault trace locations, geometry and kinematics descriptors and other available metadata have been stored. Therefore, the map offers a detailed and up-to-date depiction of the brittle deformation across the region, serving as a valuable resource for a comprehensive assessment of the seismo-tectonic framework. Moreover, the map and its accompanying database summarize fault characteristics for seismic hazard analysts and for civil protection workers, proving to be useful instruments in pinpointing areas where urgent fault research should be conducted from a seismic risk standpoint.